Occupational injuries of teachers and educational staff at special schools with multiple and severely handicapped children in Rhineland‐Palatinate (Germany): results of a cross‐sectional study. Issue 5 (31st October 2015) - Claus, Matthias; Kimbel, Renate; Letzel, Stephan; Rose, Dirk‐Matthias
Abstract : Occupational injuries of teachers and educational staff at special schools with multiple and severely handicapped children in Rhineland‐Palatinate (Germany): results of a cross‐sectional study: Matthias Claus, et al . Institute for Teachers' Health at the University Medical Center of the Johannes Gutenberg University of Mainz, Germany Objective: The present study aimed to describe the prevalence, type, and influencing factors of occupational injuries of staff working at special schools with multiple and severely handicapped pupils in Southwestern Germany. Methods: This cross‐sectional study was carried out between August 2010 and August 2012 at 13 special schools with focus on motoric and/or holistic development of handicapped pupils in Rhineland‐Palatinate (Germany). Participants were interviewed using a written questionnaire. Results: There were 395 participants (response proportion: 59.7%) in our study, with 390 being eligible for statistical analysis. Respondents were on average 45 years old and mainly female (86.9%). The 12‐month injury prevalence was 16.9%. Joint dislocations, sprains, and torn ligaments (41.6%) were the main types of injuries. Pupils (59.8%) and auxiliary equipment (12.2%) were identified as the main causes of injury by the respondents. Multivariable logistic regression analysis showed that washing pupils (using auxiliary equipment) (aOR, 3.93; 95% CI, 1.66−9.31) and daily physical strain due to unexpected conduct of pupils (aOR, 3.70; 95% CI, 1.20−11.37) were the main influencing factors for an occupational injury. Conclusions: Almost one in five persons suffered an occupational injury in the previous 12 months. Nursing activities, including close contact with pupils, were identified as the most important factors for an injury. In order to prevent injuries at special schools, a multifaceted approach is necessary. This includes sufficient supply of auxiliary devices including proper technical maintenance. Furthermore, regular participation in training for manual handling of heavy loads and schooling on the technical use of auxiliary devices should be encouraged.